Peptidylarginine deiminase from Porphyromonas gingivalis citrullinates human fibrinogen and α-enolase: implications for autoimmunity in rheumatoid arthritis. - Wegner, N; Wait, R; Sroka, A; Eick, S; Nguyen, K; Lundberg, K; Kinloch, A; Culshaw, S; Potempa, J; Venables, P (2010)
OBJECTIVE: To investigate protein citrullination by the periodontal pathogen Porphyromonas gingivalis as a potential mechanism for breaking tolerance to citrullinated proteins in rheumatoid arthritis (RA). METHODS: The expression of endogenous citrullinated proteins was analyzed by immunoblotting of cell extracts from P gingivalis and 10 other oral bacteria. P gingivalis-knockout strains lacking the bacterial peptidylarginine deiminases (PADs) or gingipains were created to assess the role of these enzymes in citrullination. Citrullination of human fibrinogen and α-enolase by P gingivalis was studied by incubating live wild-type and knockout strains with the proteins and analyzing the products by immunoblotting and mass spectrometry. RESULTS: Endogenous protein citrullination was abundant in P gingivalis but lacking in the other oral bacteria. Deletion of the bacterial PAD gene resulted in complete abrogation of protein citrullination. Inactivation of arginine gingipains, but not lysine gingipains, led to decreased citrullination. Incubation of wild-type P gingivalis with fibrinogen or α-enolase caused degradation of the proteins and citrullination of the resulting peptides at carboxy-terminal arginine residues, which were identified by mass spectrometry. CONCLUSION: Our findings demonstrate that among the oral bacterial pathogens tested, P gingivalis is unique in its ability to citrullinate proteins. We further show that P gingivalis rapidly generates citrullinated host peptides by proteolytic cleavage at Arg-X peptide bonds by arginine gingipains, followed by citrullination of carboxy-terminal arginines by bacterial PAD. Our results suggest a novel model where P gingivalis-mediated citrullination of bacterial and host proteins provides a molecular mechanism for generating antigens that drive the autoimmune response in RA.